Orbitostriatal encoding of reward delayed gratification and impulsivity in chronic pain - Mariana Cerqueira-Nunes (2024)
Central robust network functional rearrangement is a characteristic of several neurological conditions, including chronic pain. Preclinical and clinical studies have shown the importance of pain-induced dysfunction in both orbitofrontal cortex (OFC) and nucleus accumbens (NAc) brain regions for the emergence of cognitive deficits. Outcome information processing recruits the orbitostriatal circuitry, a pivotal pathway regarding contextdependent reward value encoding. The current literature reveals the existence of structural and functional changes in the orbitostriatal crosstalk in chronic pain conditions, which have emerged as a possible underlying cause for reward and time discrimination impairments observed in individuals affected by such disturbances. However, more comprehensive investigations are needed to elucidate the underlying disturbances that underpin disease development. In this review article, we aim to provide a comprehensive view of the orbitostriatal mechanisms underlying time-reward dependent behaviors, and integrate previous findings on local and network malplasticity under the framework of the chronic pain sphere.